The relationship between early life course air pollution exposure and general health in adolescence in the United Kingdom - Gergő Baranyi; Katie Harron; Youchen Shen; Kees de Hoogh; Emla Fitzsimons (Scientific Reports)
Abstract Air pollution is associated with health in childhood. However, there is limited evidence on sensitive periods during the first 18 years of life. Data were drawn from the Millennium Cohort Study, a large and nationally representative cohort born in 2000/2002. Self-reported general health was assessed at age 17; number of hospital records were derived from linked health data (Hospital Episode Statistics) for consented participants. Residential history was linked to 25 × 25 m grid resolution annual PM2.5, PM10 and NO2 maps between 2000 and 2019; year-specific air pollution exposure in 200-m buffers around postcode centroids were computed. After adjusting for individual and time-variant area-level confounders, children exposed to higher air pollution in early (2–4 y) (n = 9137; PM2.5: OR = 1.06, 95% CI: 1.01–1.11; PM10: OR = 1.05, 95% CI: 1.01–1.09; NO2: OR = 1.01, 95% CI: 1.00–1.02) and middle childhood (5–7) (n = 9171; PM2.5: OR = 1.04, 95% CI: 1.00–1.07; PM10: OR = 1.03, 95% CI: 1.01–1.06) reported worse general health at age 17. Higher PM2.5 and NO2 exposure in adolescence increased the number of hospital episodes in young adulthood. Individuals from non-White and disadvantaged backgrounds were exposed to higher levels of air pollution. Air pollution in early and middle childhood might contribute to worse general health, with ethnic minority and disadvantaged children being more exposed.